The effect of ozone fumigation and packaging type on the storability of three date palm cultivars (Phoenix dactylifera L.). - Imran , Hiba H.; Hamza, Hamza A. (Basrah Journal Of Date Palm Research, 2025)
This study was conducted on the ripened fruits of the Hedal, Khiyara, and seedling cultivar (Dakal) date palm cultivars, , which were brought from a private orchard in Hamdan region, Abu Al-Khaseeb district, south of Basra on September 5, 2024. The fruits were transferred to the Care and Storage Laboratory of the Horticulture and Landscape Design Department, where they were washed with distilled water to remove dirt and dust. Small, infected, and mechanically damaged fruits were excluded, then fumigated with three ozone periods (0, 3, 6) hours. The fruits were then packed in two types of containers: plastic container and clay one, and stored in a refrigerated incubator at 4°C for six months. . The results showed that 6-hour ozone fumigation was the most effective in reducing the percentage of fruit spoilage and weight loss for all studied varieties. It also received the highest rating in terms of sensory characteristics (shape, color, and taste). The results also showed that dates packaged in earthenware containers exhibited significantly lower percentages of fruit spoilage and improved sensory qualities, while plastic containers showed superior results in reducing weight loss. Furthermore, the results indicated an increase in the percentage of fruit spoilage, weight loss, and a decrease in sensory qualities with increasing storage time.